Implementasi dan Apresiasi Pembelajaran E-Learning Bagi Siswa SD di Masa Pandemi - Wahidi, Adam; Wuryastuti, Sri; Suratno, Tatang (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Researchers conducted an investigation into the learning dilemmas that occurred during the pandemic. Learning is conducted online using mobile phones, resulting in the lack of students' responsiveness and a long assignments collection time. In addition, it also makes students passive and less interactive due to the lack of teachers' creativity in utilizing learning media as teachers only use the Whatsapp platform. The learning activities which are limited to sharing or instructing students to read modules or worksheets (LKS) and at the end giving the task collected at a certain time triggers boredom in learning. This research discusses narrative inquiry which the results later form a narrative about the experience and findings obtained by researchers. This research focused on the field of science in grade 4 Theme 1 sub-theme 1 cares about living things. 24 students from grade 4 of SD Negeri Songgom Jaya were the subjects of this study. The object of this research is how the learning process online, how students show boredom in online learning, and the form of appreciation that students give to teachers in science learning. Instruments used in the form of interviews, videos, and images. The results of this study show that the implementation of science learning with online practice is very possible. It is even an alternative to overcome students' boredom in online learning. Before conducting the study, the researcher made an observation in advance of students' passion for caring for plants, and planting plants is their favorite as well. With the fulfillment of what they love, they give a form of appreciation not only with gratitude but with an acceptance get from them.